DEVELOPING THE VERBAL-LINGUISTIC INTELLIGENCE OF ELEMENTARY SCHOOL STUDENTS INTHE SCOPE OF FAMILY, SCHOOL AND COMMUNITY - Budi Wijaya, I Komang Wisnu (Yavana Bhasha : Journal of English Language Education, 2018)
The gold generation of 2045 is expected to bring Indonesia to reach its golden periodin 2045. Therefore, this generation needs to be complemented with human and social capital.The social capital would be pervaded if the generation has linguistic skills. Such skill wouldbe auspicious when it is equipped by verbal-linguistic intelligence. Thus, the developmentof linguistic intelligence is needed for elementary school students as part of the goldengeneration of 2045. Development of verbal-linguistic intelligence can be carried out in thefamily, school and community scopes.